2006
DOI: 10.1080/03639040500518708
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Enhancers for the Absorption of Substances Through the Skin: Laurocapram and Its Derivatives

Abstract: Absorption enhancers are substances used for temporarily increasing a membrane's permeability (e.g., the skin and mucosa), either by interacting with its components (lipids or proteins) or by increasing the membrane/vehicle partition coefficient. This article presents the results of biophysical and permeability studies performed with Laurocapram and its analogues. As shown, Laurocapram and its analogues present different enhancing efficacies, for most of both hydrophilic and lipophilic substances. The enhancin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Az is generally used at low concentrations (1-5% v/v) and its enhancer activity may be increased by using cosolvents including propyleneglycol; however, it does not show genotoxic, teratogenic, or embryotoxic effects (49). Its use for dermal administration may cause mild irritation, but for oral mucosa in low concentrations as studied in the work (1-3%) this effect may be smaller.…”
Section: Nh3mentioning
confidence: 98%
“…Az is generally used at low concentrations (1-5% v/v) and its enhancer activity may be increased by using cosolvents including propyleneglycol; however, it does not show genotoxic, teratogenic, or embryotoxic effects (49). Its use for dermal administration may cause mild irritation, but for oral mucosa in low concentrations as studied in the work (1-3%) this effect may be smaller.…”
Section: Nh3mentioning
confidence: 98%
“…Moreover, the combination of 1 Azone plus 1 PG used in the control formulation, the percutaneous permeation of sinomenine was obviously increased. The finding suggested that the enhancer activity of Azone may be increased by using cosolvents including PG 22 . As shown in Fig.…”
Section: Fig 2 Gc Chromatograms Of Ostrich Oil Obtained By Sfementioning
confidence: 92%
“…Its mechanism of action is based on its capacity to alter the organization of the lipid structure of the stratum corneum and augment the diffusion of a drug across the skin (Smith & Maibach, 1995;López-Cervantes et al, 2006). The enhancer effect of Azone ® depends predominantly on the concentration employed and the lipophilicity of the compound assayed.…”
Section: Resultsmentioning
confidence: 99%